Legal Effectivity: Transisi Electronic Commerce Pada Era Pandemi Terhadap Peraturan Pemerintah Nomor 80 Tahun 2019 - Fauzi, Maghfira Nur Khaliza; Kusworo, Daffa Ladro (Faculty of Law, Universitas Muhammadiyah Pontianak, 2021)
In the era of the Covid-19 pandemic, electronic commerce (e-commerce) helped increase economic activity in Indonesia. In conducting trade activities, e-commerce encourages a transition because it is considered more effective than conventional commerce (c-commerce) during the transition period. The increase in e-commerce users requires legal protection for consumers which requires business actors to have integrity by following business licensing regulations and standardizing services as appropriate.This research uses normative legal research methods using a statutory approach and literature study. The results of this study indicate that after the enactment of Government Regulation Number 80 of 2019 concerning Trade Through Electronic Systems, the mandate of Article 66 of Law Number 7 of 2014 concerning Trade, legally normative these regulations are considered effective in the use of e-commerce to increase legal effectiveness against applicable statutory provisions. Keywords: Transition, Government Regulation, Effectivity, E-Commerce.